2018
DOI: 10.1111/jgh.14074
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasound surveillance for cholangiocarcinoma in an endemic area: A prove of survival benefits

Abstract: Abdominal ultrasound surveillance provided survival benefits and should be considered in areas highly endemic for CCA to reduce mortality.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 26 publications
0
4
0
Order By: Relevance
“…The distant stage was present at diagnosis in 43.5% patients with iCCA, and approximately 30% in dCCA and hiCCA. Recently, Siripongsakun et al (16) reported that surveillance by abdominal ultrasound (HR, 0.41; P=0.012) was significantly provided survival benefits, suggesting highly endemic areas for CCA to apply the surveillance system. In our point of view, the surveillance system is required not only in endemic areas, but also in all patients with known risk factors for the development of CCA, such as viral hepatitis and primary sclerosing cholangitis regarding extremely high mortality of CCA.…”
Section: Discussionmentioning
confidence: 99%
“…The distant stage was present at diagnosis in 43.5% patients with iCCA, and approximately 30% in dCCA and hiCCA. Recently, Siripongsakun et al (16) reported that surveillance by abdominal ultrasound (HR, 0.41; P=0.012) was significantly provided survival benefits, suggesting highly endemic areas for CCA to apply the surveillance system. In our point of view, the surveillance system is required not only in endemic areas, but also in all patients with known risk factors for the development of CCA, such as viral hepatitis and primary sclerosing cholangitis regarding extremely high mortality of CCA.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, ultrasound surveillance can help diagnose CCA at premalignant and early cancer stages (Sungkasubun et al, 2016). Also, in this long-term surveillance cohort, Siripongsakun et al, reported a survival benefit associated with using ultrasound for CCA surveillance (Siripongsakun et al, 2018), an increased median survival from 6.7 to 31.8 months.…”
Section: Research Articlementioning
confidence: 66%
“…The ultrasound surveillance group comprised patients in the cohort of the "Study and treatment project for CCA" of Chulabhorn Hospital at Bangluang district, Nan province, during 2011-2017. (Siripongsakun et al, 2018) Whereas, the non-ultrasound surveillance group included patients with treatment of CCA at Chulabhorn Hospital during 2009-2015. (Siripongsakun et al, 2018) Both group of the patients received major investigations and treatment including Computorised Tomography (CT), Magnetic Resonance Imaging (MRI), Percuateneous Biliary Drainage (PTBD), Hepatic resection and Chemotherapy at Chulabhorn hospital.…”
Section: Methodsmentioning
confidence: 99%
“…The results showed that 3-month US detection may find more small focal lesions than 6-months US detection, but does not improve detection rate of small HCC, nor improve the 5-year survival. The efficacy of US screening every 6 months for HCC or CC in a selective high risk group in endemic areas of hepatitis B such as in Thailand, Taiwan have been reported [72][73][74] .…”
Section: Us Could Be Used For Early Detectionmentioning
confidence: 99%